1999
DOI: 10.1159/000014193
|View full text |Cite
|
Sign up to set email alerts
|

Independent and Combined Effects of Prolonged Inhaled Nitric Oxide and Oxygen on Lung Inflammation in Newborn Piglets

Abstract: Clinical use of nitric oxide (NO) is usually in conjunction with high oxygen concentrations, the effects of which may include lung neutrophil accumulation, apoptosis and upregulation of antioxidant enzyme activity. To define the effects of NO on neutrophils from young piglets and its relationship to lung neutrophil dynamics during hyperoxia we exposed thirty piglets to room air (RA), RA+NO (50 ppm NO), O2 (FiO2≥0.96) or O2+NO for 5 days. Ten additional animals breathed RA+NO or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Additionally, we hypothesized that lung CCR-2 will show a similar trend. We used a young piglet model (20) characterized by rapidly growing lungs to assess lung MCP-1 production and CCR-2 and leukocyte dynamics after 1 and 5 d of separate or concurrent exposure to NO and hyperoxia.…”
mentioning
confidence: 99%
“…Additionally, we hypothesized that lung CCR-2 will show a similar trend. We used a young piglet model (20) characterized by rapidly growing lungs to assess lung MCP-1 production and CCR-2 and leukocyte dynamics after 1 and 5 d of separate or concurrent exposure to NO and hyperoxia.…”
mentioning
confidence: 99%
“…However, studies have shown that prolonged exposure to the combination of NO and hyperoxia (NO/O 2 ) causes significantly more lung injury than hyperoxia alone in several animal models, including piglets (1) and rats (2). This increased lung injury is associated with increased apoptosis of lung cells (3). We have previously shown that exposure of cultured pulmonary cells to NO and hyperoxia causes a synergistic cytotoxicity (4), similar to that observed in lungs of exposed animals.…”
Section: Inhaled Nitric Oxide (Ino)mentioning
confidence: 79%
“…The animal exposure method has been reported previously (13,37). Briefly, we randomly separated 10-to 17-d-old piglets into three groups and placed them for 5 d in chambers that contained 1) room air (RA), 2) Ͼ95% oxygen (O 2 ), or 3) O 2 ϩ 50 ppm of NO (O 2 ϩ NO).…”
Section: Methodsmentioning
confidence: 99%
“…Hyperoxic damage to the lung is accompanied by inflammatory reactions such as leukocyte infiltration and cytokine release into the lung parenchyma (13). PDGF may be involved in this process because of its chemotactic and stimulatory effects to neutrophils and monocytes (14,15).…”
mentioning
confidence: 99%